State of health estimation of lead acid batteries in case of safety critical systems - Czibere, Szilárd; Hartmann, Bálint (GEORGIKON FOR AGRICULTURE, 2020)
The importance of energy storage has been growing rapidly nowadays. Due to this trend, the utilization of batteries has skyrocketed. The universal implementation of electricity storage is a multidisciplinary challenge for future engineering, which holds many unsolved issues currently. Thanks to improving battery technologies, batteries are also a solution for supplying safetycritical systems. Considering this type of application, knowing it is indispensable to know the exact state of these batteries. However, what are the methodologies which meet these high requirements? Batteries are complex, non-linear systems therefore knowing their adequate state is not a self-evident task. This paper reveals a methodology which can provide information about the State of Health of a battery without high capacity need. This methodology is based on a scientific empirical approach, yet industrial implementations are considered as well
Keywords: state of health estimation (SoH); batteries; energy storage; safety critical systems